Anti-plasmodial Effects of Zanthoxylum zanthoxyloides - Goodman, Christopher Dean; Hoang, An Thuy; Diallo, Drissa; Malterud, Karl Egil; McFadden, Geoffrey I.; Wangensteen, Helle (Planta Medica, 2019)
Zanthoxylum zanthoxyloides, syn. Fagara zanthoxyloides, is a tree growing in West Africa and is used in traditional medicine against a variety of diseases, including malaria. In the work reported here, root bark and stem bark extracts of this tree, as well as compounds isolated from the extracts, have been investigated for activity in vitro against chloroquine-sensitive and chloroquine-resistant strains of Plasmodium falciparum. In addition, toxicity against nauplii of the brine shrimp Artemia salina has been studied. Dichloromethane extracts of the root bark and stem bark, and a methanol extract of the stem bark, showed anti-parasitic activity towards chloroquine-sensitive as well as chloroquine-resistant P. falciparum, with IC50 values between 1 and 10 µg/mL. Among the isolated compounds, bis-dihydrochelerythrinyl ether, buesgenine, chelerythrine, γ-fagarine, skimmianine, and pellitorine were the most active, with IC50 values of less than 5 µg/mL. The dichloromethane extracts were toxic to brine shrimp nauplii, with LC50 values of less than 1 µg/mL. Methanol extracts were much less toxic (LC50 between 50 and 100 µg/mL). Among the isolated substances, bis-dihydrochelethrinyl ether was the most toxic (LC50 ca. 2 µg/mL).
Keywords: anti-malaria; Zanthoxylum zanthoxyloides; Rutaceae; alkaloids